In-silico study of the nasal cavity's influence on the pharyngeal wall pressure in anatomically-correct airway models of patients with obstructive sleep apnea - Cisonni, Julien; Lucey, Anthony; King, Andrew; Islam, S.; Goonewardene, M. (Springer International Publishing, 2013)
Repetitive brief episodes of soft-tissue collapse within the upper airway during sleep characterize obstructive sleep apnea (OSA), an extremely common and disabling disorder. Failure to maintain the patency of the upper airway is caused by the combination of sleep-related loss of compensatory dilator muscle activity and aerodynamic forces promoting closure. The prediction of soft-tissue movement in patient-specific airway 3D mechanical models is emerging as a useful contribution to clinical understanding and decision-making. Such modeling requires reliable estimations of the wall pressure forces. While nasal obstruction has been recognized as a risk factor of OSA, the need to include the nasal cavity in upper-airway models for OSA applications requires consideration, as it is most often omitted because of its complex shape. The hypothesis underpinning this work is that adequate boundary conditions and simple artificial geometric extensions can reproduce the essential effects of the nasal cavity on the pharyngeal flow field and thereby reduce the overall complexity and computational cost of accurate simulations of upper-airway dynamics.